Perovskite quantum dot Micro-LED based on interface modification and preparation method thereof

By adding bifunctional ether to the electron transport layer, an optimized electron transport layer is formed, and the bilateral interface passivation defect is used to solve the problem of insufficient optical performance and stability of perovskite quantum dot Micro-LED in display technology, achieving higher luminous efficiency and stability.

CN119630155APending Publication Date: 2025-03-14SHI-CHENG LABORATORY FOR INFORMATION DISPLAY & VISUALIZATION +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724431.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The application of perovskite quantum dots in the display technology in the prior art has problems with insufficient optical performance, stability and durability, especially under the influence of humidity, heat and light.

Method used

By adding bifunctional ether to the electron transport layer, an optimized electron transport layer is formed, and the defects of the electron transport layer and the perovskite quantum dot layer are used to passivate the defects of the electron transport layer and the perovskite quantum dot layer are improved, thereby improving the luminous efficiency and stability of the device.

Benefits of technology

The luminescence efficiency and stability of perovskite quantum dot Micro-LED is achieved, and its performance under the influence of humidity, heat and light is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630155A_ABST
    Figure CN119630155A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite quantum dot Micro-LED based on interface modification and a preparation method of the perovskite quantum dot Micro-LED. The Micro-LED structurally comprises a distributed Bragg reflector, a quantum dot color conversion unit, a GaN blue light LED and a CMOS (complementary metal oxide semiconductor) integrated circuit substrate. The GaN blue light emitting unit is composed of a plurality of blue light LED pixel points and is integrated on the CMOS integrated circuit substrate. The quantum dot color conversion unit sequentially comprises a glass substrate, a metal electrode, an electrode modification layer, an electron transport layer, a perovskite quantum dot layer, a hole transport layer, a hole injection layer, a transparent electrode and a packaging film from bottom to top, and is used for converting blue light into a required color and realizing a wider color gamut. Wherein bifunctional ether is added on the electron transport layer for optimization. The research not only can solve a plurality of problems existing in the traditional technology, but also can significantly improve the luminous efficiency and environmental stability of the device, and provides a novel and promising technical solution for the development of the next generation of high-performance Micro-LED.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of semiconductors and includes multiple aspects, such as semiconductor materials, devices, manufacturing processes and applications, etc. In particular, it relates to a perovskite quantum dot Micro-LED based on interface modification and a preparation method thereof. Background Art

[0002] Perovskite Quantum Dots (PQDs), as an emerging semiconductor material, have attracted widespread attention due to their excellent optical properties and adjustable emission wavelength. The unique crystal structure of perovskite materials enables them to have good performance in the optoelectronic field, especially in applications such as display technology, solar cells and photodetectors, showing broad prospects. The size effect of quantum dots allows their emission color to be achieved by adjusting the size and composition of the particles, thereby meeting the needs of different optoelectronic applications.

[0003] In recent years, with the rapid development of display technology, especially the rise of new display technologies such as Micro-LED and OLED, the color conversion technology of perovskite quantum dots has gradually become a research hotspot. Color conversion technology mainly uses perovskite quantum dots to convert blue light or ultraviolet light into visible light to achieve higher light output and richer color performance. By combining quantum dot materials with appropriate excitation sources, the color gamut and brightness of display devices can be effectively improved to meet the market demand for high-performance displays. In color conversion technology, perovskite quantum dots are usually prepared as thin films or coatings and combined with blue light excitation sources.

[0004] However, the process involves multiple steps, such as the synthesis of quantum dots, surface modification, and assembly on the substrate. These steps not only affect the optical properties of the final product, but also determine its stability and durability. Therefore, it is urgent to develop a perovskite quantum dot-based Micro-LED and its preparation method to overcome the shortcomings of the existing technology. Reasonable optimization is required in the material selection process structure to improve the performance of perovskite quantum dots in practical applications. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art and improve the luminous efficiency of the device, the present invention proposes a perovskite quantum dot Micro-LED based on interface modification and a preparation method thereof. By optimizing the structural design and using a bilateral interface, the defects of the electron transport layer and the perovskite quantum dot layer can be passivated at the same time, the device efficiency can be improved, and the stability of the device in terms of humidity, heat, and light can be improved.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0007] A perovskite quantum dot Micro-LED based on interface modification consists of four parts: distributed Bragg reflector, quantum dot color conversion unit, GaN blue LED array and oxide thin film transistor (TFT) substrate. Among them, the quantum dot color conversion unit includes from bottom to top: glass substrate, metal electrode, electrode modification layer, electron transport layer, perovskite quantum dot layer, hole transport layer, hole injection layer, transparent electrode and packaging film.

[0008] Specifically, the quantum dot color conversion unit includes an electron transport layer, the material of the electron transport layer is a metal oxide, and a bifunctional ether is added to the metal oxide. Different functional groups (such as carboxyl, phosphate, amino, etc.) are selected to combine with the ETL material so that the interface molecules and the ETL surface form chemical bonds or interaction forces of different strengths. By using functional groups with different polarities, the adsorption force between molecules and surfaces can be more accurately controlled.

[0009] More specifically, metal oxides include SnO2, TiO x , ZnO and other oxides together with bifunctional ethers form an optimized electron transport layer.

[0010] Specifically, the electron modification layer is deposited on the metal electrode by self-assembled monolayer, the electrode modification layer is ultrasonically cleaned with deionized water and IPA for 5 minutes, annealed at 120°C for 40 minutes in an ambient air with a RH of 12%-25%, then the bifunctional ether is dissolved in DMF, the bifunctional ether solution with a concentration of 8-12 mg / ml is spin-coated on the metal oxide at a speed of 2500-3500 rpm for 60-120 seconds, and annealed at 100°C for 20-30 minutes to obtain the final optimized electron transport layer.

[0011] More specifically, the distributed Bragg reflector of the Micro-LED based on perovskite quantum dots is placed on top of the quantum dot color conversion unit.

[0012] In further detail, the quantum dot color conversion unit is vertically placed on the GaN blue light LED, and the glass substrate is aligned with the oxide thin film transistor (TFT) substrate.

[0013] More specifically, the quantum dot color conversion unit focuses an electron beam onto a metal target in a vacuum environment, uses the high energy of the electron beam to evaporate the metal material into metal vapor, and deposits it on the surface of a glass substrate, thereby forming a dense metal electrode layer.

[0014] To be more specific, the perovskite quantum layer of the quantum dot color conversion unit is prepared by mixing CsCl, PbBr2, and CsBr in a uniform proportion in a mortar and then grinding the mixture; transferring the uniformly ground mixture to a crucible and calcining it in air; washing the calcined powder with deionized water and anhydrous ethanol, centrifuging the washed suspension, and collecting the precipitate; finally, drying the collected precipitate to obtain the perovskite quantum layer.

[0015] To be more specific, the hole transport layer of the quantum dot color conversion unit uses a solution of PVK (polyvinyl ketone) and Poly-TPD (poly(N,N'-dimethylaniline)) mixed in a ratio of 7:1, and is spin-coated on the perovskite quantum dot layer at 5000rpm for 60s using a spin coater; the hole injection layer uses a metal oxide spin-coated on the hole transport layer.

[0016] More specifically, the transparent electrode of the quantum dot color conversion unit is made of copper and indium tin oxide spray-printed on the hole injection layer.

[0017] More specifically, the material used for the packaging film of the quantum dot color conversion unit can be polyimide, polycarbonate or fluorinated polymer, which is placed on the transparent electrode.

[0018] The above-mentioned interface-modified perovskite quantum dot Micro-LED adds a bifunctional ether on the electron transport layer to obtain an optimized electron transport layer.

[0019] Beneficial effects:

[0020] 1. The present invention is based on the interface-modified perovskite quantum dot Micro-LED, and a bifunctional ether is added on the electron transport layer to form an optimized electron transport layer, wherein one functional group in the bifunctional ether can react with -OH on the surface of the metal oxide to passivate the metal oxide; the other functional group can combine with the uncoordinated lead ions in the perovskite, and inhibit non-radiative radiation by passivating the defects on the perovskite surface.

[0021] 2. The present invention is based on the interface-modified perovskite quantum dot Micro-LED, adds a bifunctional ether on the electron transport layer, and adjusts the bonding strength between the bifunctional ether interface molecules and the electron transport layer (ETL), that is, selects functional groups of different polarities (such as carboxyl, phosphate, amino, etc.) to combine with the ETL material, so that the interface molecules and the ETL surface form chemical bonds or interaction forces with different strengths, which can achieve a stronger bond between the interface molecules and the ETL, thereby weakening the bond between the interface molecules and the perovskite. This coordination of bilateral bonding can improve the efficiency of perovskite quantum dot devices and improve stability.

[0022] 3. The preparation method of the present invention has significant advantages. It does not require the use of inert gas protection and can directly synthesize perovskite quantum dots in an air environment, which greatly simplifies the operation process. At the same time, the material still shows excellent stability under high temperature conditions, overcoming the strict requirements of traditional preparation processes on atmosphere and temperature. This not only reduces the difficulty of production, but also effectively improves the overall efficiency of the device, and enhances its reliability and economy in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 A schematic diagram of the device structure of a perovskite quantum dot Micro-LED based on interface modification;

[0025] Figure 2 A schematic diagram of the structure of a color conversion unit of a perovskite quantum dot Micro-LED based on interface modification;

[0026] Figure 3 is the chemical structural formula of some difunctional ether materials;

[0027] Figure 4 JVL curves of the perovskite light-emitting diodes prepared in Examples 1 and 2 and the comparative example;

[0028] Figure 5 J-EQE curves of the perovskite light-emitting diodes prepared in Examples 1 and 2 and the comparative example. DETAILED DESCRIPTION

[0029] Next, the technical solution will be described in detail and completely in conjunction with the accompanying drawings in the embodiments of the present invention. It should be clear that the embodiments only represent some examples of the present invention, not all examples. According to the embodiments of the present invention, any other embodiments that can be derived before the technical personnel in this field perform creative work are within the protection scope of the present invention.

[0030] Example 1

[0031] In this embodiment 1, the device structure is: a distributed Bragg reflector 1, a quantum dot color conversion unit 2, a GaN blue light LED array 3 and an oxide thin film transistor (TFT) substrate 4, such as Figure 1 shown.

[0032] The quantum dot color conversion unit 2 includes, from bottom to top, a glass substrate 5, a metal electrode 6, an electrode modification layer 7, an electron transport layer 8, a perovskite quantum dot layer 9, a hole transport layer 10, a hole injection layer 11, a transparent electrode 12, and a packaging film 13; the direction indicated by the arrow in the figure is the actual light emitting direction of the pixel, such as Figure 2 shown.

[0033] The specific preparation process is as follows:

[0034] a. Distributed Bragg reflector: First, use a spectrometer to test its reflection wavelength and reflectivity to obtain actual reflection spectrum data. Then compare and analyze the test results in detail with the designed target parameters to evaluate whether the performance of the reflector meets the design requirements and ensure that it can provide the best reflection efficiency within the predetermined wavelength range, thereby ensuring the stability and efficiency of the overall optical system.

[0035] b. Quantum dot color conversion unit:

[0036] 1. Select a suitable glass substrate, thoroughly clean and treat the surface, and align it with the oxide thin film transistor (TFT) substrate;

[0037] 2. Focus the electron beam onto the metal target in a vacuum environment, use the high energy of the electron beam to evaporate the metal material into metal vapor, and deposit it on the surface of the glass substrate to form a dense metal electrode layer;

[0038] 3. The electron modification layer is evaporated on the metal electrode using a self-assembled monolayer. The electrode modification layer is ultrasonically cleaned with deionized water and IPA for 5 minutes, annealed at 120°C for 40-60 minutes in an ambient air with a RH of 18%-23%. Then, 2,2'-oxydiethylamine is dissolved in DMF, and a 2,2'-oxydiethylamine solution with a concentration of 8-12 mg / ml is spin-coated on the metal oxide SnO2 at a speed of 2500-3500 rpm for 60-120 seconds, and annealed at 100°C for 20-30 minutes. To obtain the final optimized electron transport layer. The molecular structure of 2,2'-oxydiethylamine is as follows: Figure 3 As shown;

[0039] 4. The perovskite quantum dot material is mixed and ground by 100-127 mg of PbBr2, 34-56 mg of CsCl and 20-27 mg of CsBr to ensure that it is fully uniform. The mixture is transferred to a corundum crucible and calcined at 600 ° C for 20 minutes in an air environment. The calcined product is then washed with deionized water and anhydrous ethanol, and then centrifuged at 8000 rpm / min for 5 minutes to collect the precipitate. Finally, the collected precipitate is dried at 50 ° C for 4-8 hours to obtain a perovskite quantum dot layer;

[0040] 5. The hole transport layer is made of a solution of PVK (polyvinyl ketone) and Poly-TPD (poly (N, N'-dimethylaniline)) mixed in a ratio of 7:1, and is spin-coated on the perovskite quantum dot layer using a spin coater at 5000rpm for 60s, and is deposited on the perovskite quantum dot layer by a spin coating process. The hole injection layer is made of tungsten oxide (WO3), which is also deposited on the hole transport layer by a spin coating process;

[0041] 6. The transparent electrode layer is printed by spraying indium tin oxide onto the surface of the hole injection layer, and finally epoxy resin is used as the packaging material to cover the top of the transparent electrode to complete the packaging.

[0042] c.GaN blue LED array: The array consists of blue light-emitting diode (LED) chips made of gallium nitride (GaN) material, each chip is the core unit for achieving light emission. These chips contain GaN material layers that can produce blue light sources and are arranged in an array structure to provide a stronger light-emitting effect.

[0043] d. The process of making oxide thin film transistor substrates includes the following steps: First, the glass or silicon substrate is cleaned to remove contamination; then, the oxide semiconductor layer IGZO is deposited, which is completed by chemical vapor deposition (CVD). Next, photolithography and etching processes are used to form electrode and channel patterns; subsequently, the gate insulating layer silicon dioxide is deposited, and then the metal material is deposited as the gate and patterned. Finally, the source and drain electrodes are deposited to define their patterns.

[0044] Example 2

[0045] In this embodiment 2, the device structure is: a distributed Bragg reflector 1, a quantum dot color conversion unit 2, a GaN blue light LED array 3 and an oxide thin film transistor substrate 4, such as Figure 1 shown.

[0046] The quantum dot color conversion unit 2 includes, from bottom to top, a glass substrate 5, a metal electrode 6, an electrode modification layer 7, an electron transport layer 8, a perovskite quantum dot layer 9, a hole transport layer 10, a hole injection layer 11, a transparent electrode 12, and a packaging film 13; the direction indicated by the arrow in the figure is the actual light emitting direction of the pixel, such as Figure 2 shown.

[0047] The specific preparation process is as follows:

[0048] a. Distributed Bragg reflector: First, use a spectrometer to test its reflection wavelength and reflectivity to obtain actual reflection spectrum data. Then compare and analyze the test results in detail with the designed target parameters to evaluate whether the performance of the reflector meets the design requirements and ensure that it can provide the best reflection efficiency within the predetermined wavelength range, thereby ensuring the stability and efficiency of the overall optical system.

[0049] b. Quantum dot color conversion unit:

[0050] 1. Select a suitable glass substrate, clean it thoroughly, treat its surface, and align it with the oxide thin film transistor substrate;

[0051] 2. Focus the electron beam onto the metal target in a vacuum environment, use the high energy of the electron beam to evaporate the metal material into metal vapor, and deposit it on the surface of the glass substrate to form a dense metal electrode layer;

[0052] 3. The electron modification layer is evaporated on the metal electrode using a self-assembled monolayer. The electrode modification layer is ultrasonically cleaned with deionized water and IPA for 5 minutes, annealed at 120°C for 40-60 minutes in an ambient air with a RH of 18%-23%. Subsequently, 2,2'-oxybis(acetic acid) is dissolved in DMF, and a 10-12 mg / ml 2,2'-oxydiethylamine solution is spin-coated on the metal oxide SnO2 at a speed of 3000-3500 rpm for 60-90 seconds, and annealed at 100°C for 25-30 minutes to obtain the final optimized electron transport layer. The molecular structure of 2,2'-oxybis(acetic acid) is as follows: Figure 3 As shown;

[0053] 4. The perovskite quantum dot material is mixed and ground by 100-127 mg of PbBr2, 34-56 mg of CsCl and 20-27 mg of CsBr to ensure that it is fully uniform. The mixture is transferred to a corundum crucible and calcined at 600 ° C for 20 minutes in an air environment. The calcined product is then washed with deionized water and anhydrous ethanol, and then centrifuged at 8000 rpm / min for 5 minutes to collect the precipitate. Finally, the collected precipitate is dried at 50 ° C for 4-8 hours to obtain a perovskite quantum dot layer;

[0054] 5. The hole transport layer is made of a solution of PVK (polyvinyl ketone) and Poly-TPD (poly (N, N'-dimethylaniline)) mixed in a ratio of 7:1, and is spin-coated on the perovskite quantum dot layer using a spin coater at 5000rpm for 60s, and is deposited on the perovskite quantum dot layer by a spin coating process. The hole injection layer is made of tungsten oxide (WO3), which is also deposited on the hole transport layer by a spin coating process;

[0055] 6. The transparent electrode layer is printed by spraying indium tin oxide onto the surface of the hole injection layer, and finally epoxy resin is used as the packaging material to cover the top of the transparent electrode to complete the packaging.

[0056] c.GaN blue LED array: The array consists of blue light-emitting diode (LED) chips made of gallium nitride (GaN) material, each chip is the core unit for achieving light emission. These chips contain GaN material layers that can produce blue light sources and are arranged in an array structure to provide a stronger light-emitting effect.

[0057] d. The process of making oxide thin film transistor substrates includes the following steps: First, the glass or silicon substrate is cleaned to remove contamination; then, the oxide semiconductor layer IGZO is deposited, which is completed by chemical vapor deposition (CVD). Next, photolithography and etching processes are used to form electrode and channel patterns; subsequently, the gate insulating layer silicon dioxide is deposited, and then the metal material is deposited as the gate and patterned. Finally, the source and drain electrodes are deposited to define their patterns.

[0058] Comparative Example

[0059] In this comparative example, only the configuration of the electron transport layer in step b-3 is different from that in the embodiment, in which the bilateral interface harmony strategy is not adopted, and the SnO2 is not spin-coated with a bifunctional ether. The remaining steps are the same as those in embodiment 1.

[0060] Performance Test:

[0061] Devices were made from Examples 1, 2 and the comparative example, and electrical properties such as current density, voltage, brightness, and EQE were tested. The JVL curves obtained are shown in FIG. Figure 4 As shown, the J-EQE curve is as follows Figure 5 shown.

[0062] Depend on Figure 5 It can be seen that the current density and brightness of the device with the addition of the bilateral interface harmony strategy are increased, because one functional group can react with the -OH on the surface of the metal oxide to passivate the metal oxide. The other functional group can combine with the uncoordinated lead ions in the perovskite, thereby passivating the non-radiative recombination center and promoting the injection and transport of carriers.

[0063] Depend on Figure 5 It can be seen that the EQE of devices that add bilateral interface harmony strategies has an upward trend. This is because by adding bifunctional ethers on the electron transport layer, by adjusting the bonding strength between the bifunctional ether interface molecules and the electron transport layer (ETL), a stronger bond between the interface molecules and the ETL can be achieved, thereby weakening the bond between the interface molecules and the perovskite. This bilateral bonding coordination can improve the efficiency of perovskite perovskite quantum dot devices, improve stability, and enhance device performance.

[0064] The terms mentioned in this specification, such as "Example 1", "Example 2", "Comparative Example", etc., all refer to at least one embodiment or example related to specific features, structures, materials or characteristics. It should be noted that the expressions of these terms do not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in an appropriate manner.

[0065] The above content shows the basic principles, main features and advantages of the present invention. Those skilled in the art should be aware that the present invention is not limited to the above embodiments, and the described embodiments are only used to illustrate the principles of the present invention. Various changes and improvements may occur without departing from the spirit and scope of the present invention, and these changes and improvements are within the scope of protection of the present invention.

Claims

1. A perovskite quantum dot Micro-LED based on interface modification, characterized in that: From top to bottom, it includes a distributed Bragg reflector, a quantum dot color conversion unit, a GaN blue light LED array and an oxide thin film transistor substrate. The quantum dot color conversion unit includes from bottom to top: a glass substrate, a metal electrode, an electrode modification layer, an electron transport layer, a perovskite quantum dot layer, a hole transport layer, a hole injection layer, a transparent electrode, and a packaging film; the electron transport layer includes a metal oxide and a bifunctional ether.

2. The interface-modified perovskite quantum dot Micro-LED according to claim 1, characterized in that: The bifunctional ether comprises two mutually symmetrical functional groups, and the functional groups are carboxyl groups, phosphoric acid groups or amino groups.

3. The interface-modified perovskite quantum dot Micro-LED according to claim 1, characterized in that: The metal oxide is SnO2, TiO x or ZnO.

4. The method for preparing the interface-modified perovskite quantum dot Micro-LED according to any one of claims 1 to 3, characterized in that: The steps include: The electronic modification layer is deposited on the metal electrode using a self-assembled monolayer; Clean the electrode modification layer and perform annealing in an ambient air with a RH of 12%-25%; Dissolving the difunctional ether in DMF to obtain a difunctional ether solution with a concentration of 8-12 mg / ml; The bifunctional ether solution is spin-coated on the metal oxide at a rotation speed of 2500-3500 rpm for 60-120 seconds, and annealed to obtain a final optimized electron transport layer.

5. The preparation method according to claim 4, characterized in that: The quantum dot color conversion unit adopts electron beam evaporation method, which focuses the electron beam on the metal target in a vacuum environment, uses the high energy of the electron beam to evaporate the metal material into metal vapor, and deposits it on the surface of the glass substrate, thereby forming a dense metal electrode layer.

6. The preparation method according to claim 4, characterized in that: The quantum dot color conversion unit is prepared by mixing CsCl, PbBr2 and CsBr in a mortar in a uniform proportion and then grinding them; transferring the uniformly ground mixture to a crucible and calcining it in air; washing the calcined powder with deionized water and anhydrous ethanol, centrifuging the washed suspension and collecting the precipitate; and finally drying the collected precipitate to obtain a perovskite quantum layer.

7. The preparation method according to claim 4, characterized in that: The hole transport layer of the quantum dot color conversion unit adopts a solution of polyvinyl ketone and poly (N, N'-dimethylaniline) with a mixing ratio of 7:1, which is spin-coated on the perovskite quantum dot layer; the hole injection layer adopts metal oxide spin-coated on the hole transport layer.

8. The preparation method according to claim 4, characterized in that: The transparent electrode of the quantum dot color conversion unit is made of copper and indium tin oxide sprayed and printed on the hole injection layer.

9. The preparation method according to claim 4, characterized in that: The material used for the packaging film of the quantum dot color conversion unit is polyimide, polycarbonate or fluorinated polymer, and is placed on the transparent electrode.

10. The preparation method according to claim 4, characterized in that: By selecting functional groups of different polarities to combine with metal oxides, chemical bonds or interaction forces of different strengths are formed between the interface molecules and the surface of the metal oxide.